Kesantunan Berbahasa dalam Komunikasi Grup Whatsapp Pemerintah Desa: Tinjauan Prinsip Leech - Dania Kusuma Wardani; Salsa Devista Mayangsari; Taswirul Afkar (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
This study aims to identify the application and violation of the principles of politeness according to Geoffrey Leech in the village government WhatsApp group communication. The phenomenon of language use in institutional digital communication often ignores the elements of politeness, even though communication is carried out in a professional context. This study uses a descriptive qualitative approach with a case study method. The data studied are in the form of speech or written messages sent by members of the Bendung Village Government WhatsApp group, Jetis District, Mojokerto Regency. Data collection techniques are carried out through reading and note-taking techniques, while data analysis is carried out using interactive analysis techniques including data reduction, data presentation, and drawing conclusions. The results of the study show the application of the six maxims in communication in the village government WhatsApp Group based on Geoffrey Leech's principles of politeness, between the maxim of agreement, the maxim of wisdom, the maxim of praise, the maxim of generosity, the maxim of sympathy, and the maxim of humility appearing in forms of communication. This application shows that digital media does not eliminate the values of politeness, but rather becomes an adaptation of a more flexible but ethical communication strategy. Furthermore, micro-frequencies of violations of the maxim of agreement, the maxim of wisdom and the maxim of sympathy were also found in the context of conveying sensitive, technical or administrative information. This study emphasizes the importance of awareness of polite language in official digital communication, especially in the village bureaucratic environment.